Statutory Insolvency Regulations and Earnings Management in the Prepaid Health-Care Industry - Mensah, Yaw M.; Considine, Judith M.; Oakes, Leslie (The Accounting Review, 1994)
[Although health-care reform has emerged recently as an important national priority, there has been little research on the effect of possible deficiencies in both accounting and auditing standards in the development of problems in this area. This study examines earnings management in the health maintenance organization (HMO) sector of the prepaid health-care industry. HMOs are a principal component of the managed health-care concept currently being promoted as important in controlling escalating health-care costs. The study examines possible strategic behavior by HMO management in the accrual of "incurred but not reported expenses" (IBNRs). IBNRs are the costs of medical care provided to HMO enrollees during a given year but not yet reported to the HMO by the fiscal year-end. They consist primarily of five components: accrued inpatient hospitalization costs, accrued primary physician costs, accrued costs from medical specialists to whom HMO enrollees have been referred, accrued medical incentive pool payments, and other miscellaneous medical costs. Their accrual was first recommended by the Health Maintenance Organization Task Force of the American Institute of Certified Public Accountants in an issues paper later published as an exposure draft (AICPA 1985). It was eventually released as SOP 89-5 entitled Financial Accounting and Reporting by Providers of Prepaid Health Services in 1989 to be effective for fiscal years beginning on or after 15 June 1989 with earlier application encouraged. However, by the time SOP 89-5 was issued, a significant majority of HMOs was already in compliance with the SOP, at least so far as the accrual of IBNRs was concerned. The results of this study suggest that IBNRs may have been used as part of a strategic response by HMO management to events specific to the industry in the 1986-1989 period. These events included the outbreak of a premium war apparently waged to obtain market share at the expense of immediate profitability and the enactment in many states of minimum net worth regulations designed to prevent the resultant increase in financial failures among HMOs. The results suggest that the IBNRs were systematically understated by financially weaker HMOs (relative to their stronger counterparts) in order to minimize regulatory costs associated with the statutory minimum net worth requirements imposed by some states during this period. Furthermore, the results were also consistent with the political visibility hypothesis, which theorizes that highly profitable firms in politically sensitive sectors seek to reduce their visibility by adopting income-decreasing accounting methods and discretionary accruals. However, the findings were not consistent with the political visibility hypothesis if size is visualized as a proxy for political visibility.]